Carotid intima-media thickness- A surrogate marker for coronary artery disease in the South African black population? - Holland, Zaiboonnisa (My University, 2006)
B-mode ultrasound measurement of the carotid intima-media thickness (CIMT) has been convincingly shown to be a predictor of coronary artery disease (CAD) in several studies. To my knowledge such assessments have not been carried out in the Black South African population, which hitherto had a low prevalence of CAD. However, with the increases in prevalence of a cluster of risk factors categorised as the Metabolic Syndrome (MS), CAD is inevitably on the increase. The purpose of this study was to evaluate the role of CIMT in predicting CAD in Black South Africans, and to correlate CIMT with the known risk factors for CAD, including those of the MS. My study has shown that CIMT predicts the extent of CAD as found at coronary angiography. Multiple regression analysis identified hypertension and fasting glucose as the most important determinants of CIMT. Age, obesity, smoking and LDL-Cholesterol also correlated positively with CIMT. The results suggest that in this population, hypertension and diabetes are crucial in the pathogenesis of thickening of the intima-media of carotid arteries, a surrogate marker of coronary artery disease.
Faculty of Health Sciences School of Clinical Medicine 0420355x Zaiboon@hotmail.com
Keywords: CIMT; CAD